2011
DOI: 10.1124/dmd.111.040949
|View full text |Cite
|
Sign up to set email alerts
|

Human Metabolism of Lapatinib, a Dual Kinase Inhibitor: Implications for Hepatotoxicity

Abstract: ABSTRACT:Lapatinib (Tykerb, Tyverb) is an important orally active dual tyrosine kinase inhibitor efficacious in combination therapy for patients with progressive human epidermal receptor 2-overexpressing metastatic breast cancer. However, clinically significant liver injury, which may be associated with lapatinib metabolic activation, has been reported. We describe the metabolism and excretion of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
94
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 27 publications
10
94
0
Order By: Relevance
“…3, HLM, rCYP3A4, and rCYP3A5 all converted lapatinib to 10 components (M1 through M10). Consistent with the results of previous in vitro (Teng et al, 2010) and in vivo studies (Castellino et al, 2012), the primary metabolites of lapatinib (M1, M3, M4, M8, and M10) were formed by N-dealkylation (M4 and M10), O-dealkylation (M1), N-hydroxylation (M8), or C-hydroxylation (M3). These and other oxidation reactions converted the five primary metabolites to four secondary metabolites (M2, M5, M6, and M7) and one tertiary metabolite (M9), as shown in Fig.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…3, HLM, rCYP3A4, and rCYP3A5 all converted lapatinib to 10 components (M1 through M10). Consistent with the results of previous in vitro (Teng et al, 2010) and in vivo studies (Castellino et al, 2012), the primary metabolites of lapatinib (M1, M3, M4, M8, and M10) were formed by N-dealkylation (M4 and M10), O-dealkylation (M1), N-hydroxylation (M8), or C-hydroxylation (M3). These and other oxidation reactions converted the five primary metabolites to four secondary metabolites (M2, M5, M6, and M7) and one tertiary metabolite (M9), as shown in Fig.…”
Section: Resultssupporting
confidence: 78%
“…Lapatinib was recently identified as an irreversible inhibitor of CYP3A5 (Chan et al, 2012) and a quasi-irreversible inhibitor of CYP3A4; the latter is associated with the formation of a ;455-nm absorbing MI complex (Takakusa et al, 2011). In addition, several stable Noxygenation metabolites of lapatinib have been reported both in vitro (Takakusa et al, 2011) and in vivo (Castellino et al, 2012). These findings suggest that lapatinib is converted to a nitroso metabolite that complexes with ferrous CYP3A4 (but not CYP3A5) and that the intervening metabolites might be sufficiently stable to provide information on the metabolic pathway leading to nitroso formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, our data provided a new therapy strategy for treatments of patients overexpressing MRP1. In addition, lapatinib is metabolized by human liver P450s to form O-and N-dealkylated metabolites (52). Some reports showed that lapatinib was an irreversible inhibitor of CYP3A4 and formed a metabolic intermediate (MI) complex with the latter, and the inhibition of CYP3A4 is a major cause of drug-to-drug interactions (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…9. Allitinib shared several metabolic pathways with its analog lapatinib (Castellino et al, 2012), including the O-dealkylation and hydroxylation of the quinazoline moiety. However, the major metabolic sites of allitinib are located at the a,b-unsaturated carbonyl group, and include amide hydrolysis and dihydrodiol formation.…”
Section: Metabolism Of Allitinib In Humans 881mentioning
confidence: 99%